2022
DOI: 10.1155/2022/9613095
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of HULC Induces Ferroptosis in Hepatocellular Carcinoma via Targeting of the miR-3200-5p/ATF4 Axis

Abstract: Hepatocellular carcinoma is a malignant tumor that poses a serious threat to human health. Ferroptosis, which represents an identified type of regulated iron-dependent cell death, may play an important role in hepatocellular carcinoma. However, it is unclear as to whether ferroptosis is involved with the mechanisms of lncRNA HULC in liver cancer cells. Here, we show that knockdown of HULC increases ferroptosis and oxidative stress in liver cancer cells. We also found changes in some related miRNAs in cells tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Inhibition of the expression of Slc7a11 could affect the activity of Gpx4, induce decline of GSH and accumulation of lipid ROS, and finally lead to ferroptosis [19]. Atf4, activating transcription factor 4, is a member of DNA-binding proteins that includes the AP-1 family of transcription factors, cAMP-response element binding proteins (CREBs) and CREB-like proteins [20][21][22][23]. Atf4 presented a protective role in oxidative stress and endoplasmic reticulum stress [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the expression of Slc7a11 could affect the activity of Gpx4, induce decline of GSH and accumulation of lipid ROS, and finally lead to ferroptosis [19]. Atf4, activating transcription factor 4, is a member of DNA-binding proteins that includes the AP-1 family of transcription factors, cAMP-response element binding proteins (CREBs) and CREB-like proteins [20][21][22][23]. Atf4 presented a protective role in oxidative stress and endoplasmic reticulum stress [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…To date, extensive evidence has shown that lncRNAs could act as a molecular sponge for miRNAs in cancers via the ceRNA mechanism to modulate ferroptosis. For example, lncRNAs HULC in HCC induced ATF4 stability by competitively binding to miR-3200-5p, resulting in the inhibition of ferroptosis ( Guan et al, 2022 ). Among these lncRNAs, we found that nine possible lncRNAs in HCC were screened through the starBase database, and the high activity of both DUXAP8 and LINC00511 within HCC had poorer survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…miR-362-3p can promote the expression of MIOX and increase ferroptosis to alleviate the progression of liver cancer [45]. miR-3200-5p regulates liver cancer progression by targeting ATF4 to induce ferroptosis [46]. In recent years, several mediators involved in ferroptosis have been reported, including the accumulation of ROS, consumption of GSH, suppression of GPX4 activity, and elevated release of polyunsaturated fatty acids [47][48][49].…”
Section: Discussionmentioning
confidence: 99%